Vagus nerve stimulation balanced disrupted default-mode network and salience network in a postsurgical epileptic patient - Wang KL; Chai Q; Qiao H; Zhang JG; Liu TH; Meng FG (Neuropsychiatric Disease and Treatment)
Kailiang Wang,1,2 Qi Chai,1 Hui Qiao,1 Jianguo Zhang,2,3 Tinghong Liu,1,2 Fangang Meng,1,2 1Beijing Neurosurgical Institute, Capital Medical University, 2Beijing Key Laboratory of Neurostimulation, 3Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China Introduction: In recent years, treatment of intractable epilepsy has become more challenging, due to an increase in resistance to antiepileptic drugs, as well as diminished success following resection surgery. Here, we present the case of a 19-year old epileptic patient who received vagus nerve stimulation (VNS) following unsuccessful left parietal–occipital lesion-resection surgery, with results indicating an approximate 50% reduction in seizure frequency and a much longer seizure-free interictal phase. Materials and methods: Using resting-state functional magnetic resonance imaging, we measured the changes in resting-state brain networks between pre-VNS treatment and 6 months post-VNS, from the perspective of regional and global variations, using regional homogeneity and large-scale functional connectives (seeding posterior cingulate cortex and anterior cingulate cortex), respectively. Results: After 6 months of VNS therapy, the resting-state brain networks were slightly reorganized in regional homogeneity, mainly in large-scale functional connectivity, where excessive activation of the salience network was suppressed, while at the same time the suppressed default-mode network was activated. Conclusion: With regard to resting-state brain networks, we propose a hypothesis based on this single case study that VNS acts on intractable epilepsy by modulating the balance between salience and default-mode networks through the integral hub of the anterior cingulate cortex. Keywords: vagus nerve stimulation, epilepsy monitoring, epilepsy surgery, functional neuroimaging, brain-network balance